A simulation based analysis of inventory management - Han, Dafei (2014)
A new raw material inventory management policy is applied in Blue Brick recently. The policy is designed to fully utilize the free-storage time allowance of port and reduce raw material inventory in the external warehouse. Simulations have been run to anticipate the inventory management performance of paperboard A which is mostly used in Blue Brick. The results of stock-out probability, external warehouse shipping cost, external warehouse storage cost help the company determine optimized policy parameters.